2019
DOI: 10.1136/annrheumdis-2019-216658
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional TEM cells in psoriatic arthritis synovium skewed towards Th17 cells

Abstract: Correspondenceare skewed more towards the Th17 cells when compared with RA. At different time points of a disease process, it is expected that the kinetics of the polyfunctionality of these cells along with their cytokine profile would vary. Thus, this could be a possible explanation for treatment failure or variations in responsiveness to a specific anticytokine therapeutic agent in a patient with RA or in a patient with PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…We have adopted the term polyfunctional from the work by others [35][36][37] acknowledging that this may be a suboptimal term as the production of cytokines is arguably a single function. MAIT cells have been shown to express several lineage transcription factors providing them with the capacity to produce multiple cytokines without following the Th1/Th2/Th17 paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…We have adopted the term polyfunctional from the work by others [35][36][37] acknowledging that this may be a suboptimal term as the production of cytokines is arguably a single function. MAIT cells have been shown to express several lineage transcription factors providing them with the capacity to produce multiple cytokines without following the Th1/Th2/Th17 paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Tyk2 and JAKs are recruited by multiple cytokines (Fig. 2) which influences several following possible functions of T cells which are required for immune-mediated inflammation in autoimmune disease [4,5,6 ▪▪ ,7–9,10 ▪ ,14,15]:…”
Section: Regulatory Role Of the Janus Kinase–signal Transducers And A...mentioning
confidence: 99%
“…Integrated interactions of antigen-presenting cells with T-cell phenotypes along with adhesion molecules, and lesional cytokines develop inflammatory proliferative cascades which lead to diverse clinical phenotypes for SpA [1,4,5]. The activated T cells regulate the local tissue response and damage through their cytokines and an integrated interaction with multiple inflammatory cells with innate functions such as macrophages and neutrophils [1,6 ▪▪ ,7,8]. It is also well-demonstrated that cytokines have crucial functions in the development, differentiation, and regulation of the immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Th17 cells play a significant role in various autoimmune and inflammatory diseases [1,2]. Several recent studies link CD146 (MCAM-melanoma cell adhesion molecule) expression with Th17 effector function.…”
Section: Introductionmentioning
confidence: 99%